2015
DOI: 10.1002/app.42402
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l‐lactic acid) with the organic nucleating agent N,N,N′‐tris(1H‐benzotriazole) trimesinic acid acethydrazide: Crystallization and melting behavior

Abstract: N,N,N 0 -Tris(1H-benzotriazole) trimesinic acid acethydrazide (BD) was synthesized from 1H-benzotriazole acetohydrazide and trischloride to serve as an organic nucleating agent for the crystallization of poly(L-lactic acid) (PLLA). First, the thermogravimetric analysis of BD exhibited a high thermal decomposition temperature; this indicated that BD maybe used as a heterogeneous nucleating agent of PLLA. Then, the effect of BD on the crystallization and melting behavior of PLLA was investigated through differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The highintensity peaks at 367.13 and 373.14 eV correspond to Ag + ions, whereas the lowintensity peaks at 367.97 and 373.98 eV are associated with metallic Ag. [55][56][57][58][59][60] In the formed Ag/Ag 3 PO 4 heterostructure, the amount of metal Ag in the microcrystals samples is considerably variable, i.e., the metallic Ag content for the pAP, eAP, and lAP samples was calculated, considering a mean area of metallic silver on the surface of the samples, to be 18.86%, 23.12%, and 19.85%, respectively. A higher metal Ag 0 content is observed on the surface of the eAP sample, which is possibly associated with the larger amount fixed to the surface of the microcrystal; this is confirmed by the measurements of the scanning microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The highintensity peaks at 367.13 and 373.14 eV correspond to Ag + ions, whereas the lowintensity peaks at 367.97 and 373.98 eV are associated with metallic Ag. [55][56][57][58][59][60] In the formed Ag/Ag 3 PO 4 heterostructure, the amount of metal Ag in the microcrystals samples is considerably variable, i.e., the metallic Ag content for the pAP, eAP, and lAP samples was calculated, considering a mean area of metallic silver on the surface of the samples, to be 18.86%, 23.12%, and 19.85%, respectively. A higher metal Ag 0 content is observed on the surface of the eAP sample, which is possibly associated with the larger amount fixed to the surface of the microcrystal; this is confirmed by the measurements of the scanning microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that PLLA/1% SrP presents higher than the pristine PLLA. The reason is that the incorporation of SrP makes PLLA form more regular structure in cooling crystallization, and these regular structures firstly need to be destroyed before the glass transition of PLLA occurs, resulting in the increase of from 56.5 ∘ C to 59.6 ∘ C. The similar result also can be observed in PLLA/N,N,N -tris(1H-benzotriazole) trimesinic acid acethydrazide system [10].…”
Section: Nonisothermal Crystallizationmentioning
confidence: 52%
“…Especially with the worse environmental pollution day by day, PLLA will become important general-purpose plastics and be employed in more industry and daily life fields. However, so far there are still some challenges, such as slow crystallization rate and poor heat resistance [10], to restrict the development of PLLA industry. In the case of application, it is a fact that improvement of PLLA crystallization rate is very critical.…”
mentioning
confidence: 99%
“…The nucleating agent can instantaneously increase the nucleation density in PLLA matrix and reduce the surface free energy barrier to induce the crystallization to occur in the higher temperature region or at a faster cooling rate. As a result, the crystallization of PLLA has been improved by a large amount of effective nucleating agents such as talc [12], montmorillonite [13], mica [14], halloysite [15], calcium carbonate [16], zinc citrate [17], silicon dioxide [18], grapheme [19], YVO4 [20], metal phosphonate [21], zinc salts of amino acids [22], metallic salts of phenylmalonic acid [23], p-tert-butylcalix [8]arene [24], myo-inositol [25], sorbitol derivative [26,27], fulvic acid amide [28], benzoyl hydrazine derivatives [29,30], 1H-benzotriazole derivatives [31], etc. Through analysis of progress in nucleating agents for PLLA, it was found that the nucleating agent for PLLA gradually evolved from inorganic compounds to organic compounds [32].…”
Section: Introductionmentioning
confidence: 99%